THE EFFECT OF SELF-EFFICACY ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) EMPLOYEES OF INSTITUT AGAMA ISLAM NEGERI KENDARI - Syamsuddin Syamsuddin; La Ringgasa La Ringgasa; Badarwan Badarwan (Langkawi: Journal of The Association for Arabic and English, 2017)
The problem studied in this research is whether self-efficacy has direct effect on Organizational Citizenship Behavior. The research method was done by using quantitative approach through survey method by collecting data through research instrument, and spreading questionnaire to the employee which the result then processed through SPSS program to know the influence between variables. The population in this study amounted to 103 people and a sample of 82 employees and lecturers who received additional duties as structural officials IAIN Kendari. Based on the results of this study, it is found that there is a direct positive effect of self-efficacy on IAIN Kendari organizational Citizenship Behavior (OCB) of 0.471 or self-efficacy had an effect on Organizational Citizenship Behavior (OCB) IAIN employees Kendari with 47.1%. Therefore, it is concluded that empowerment and self-efficacy have a direct positive and significant impact on IAIN Kendari Organizational Citizenship Behavior (OCB).